Don't knock the rock [videorecording (DVD)] - Sears, Fred F.; Haley, Bill, 1925-1981; Dale, Alan, 1926-2002; Freed, Alan; Little Richard, 1932-2020-; Appell, Dave (Double feature, 2006)
A rock and roller is out to prove that rock 'n' roll is not dangerous.